Mitigasi Academic Transition Anxiety Berbasis Sistem Kuliyyatul Mu’allimin al-Islamiyah pada Santri Baru Pesantren Modern - Gheapani Tri Yanuar; Lutfi Faishol (Scidacplus, 2026)
Academic Transition Anxiety (ATA) is a significant psychological phenomenon among new students, particularly in Islamic boarding schools (pesantren) environments that require students to adapt to new academic, social, and spiritual systems simultaneously. This study aims to analyze the ATA mitigation strategies based on the Kuliyyatul Mu’allimin al-Islamiyah (KMI) system at the Daarul Huda Banjar Patroman Modern Islamic Boarding School. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participant observation, and documentation from new students, homeroom teachers, and boarding school administrators. Data analysis employed the interactive model of Miles, Huberman, and Saldaña (2014). The results revealed three main mitigation pillars: (1) adaptive curriculum design through the KMI-national dual curriculum with a gradual language scaffolding strategy; (2) a continuous and personalized academic mentoring system through homeroom teachers and evening study programs; and (3) a comprehensive 24-hour dormitory system integrated with a structured orientation program (Khutbatul Arsy). These findings demonstrate that the KMI system functions not only as a pedagogical framework but also as a holistic ecosystem that supports adaptive psychological management for new students. This research contributes to an empirically based model for ATA mitigation within the context of modern Islamic boarding school education that is culturally relevant and contextually appropriate.